Abnormal spontaneous regional brain activity in primary insomnia: a resting-state functional magnetic resonance imaging study - Li C; Ma X; Dong M; Yin Y; Hua K; Li M; Li C; Zhan W; Li C; Jiang G (Neuropsychiatric Disease and Treatment, 2016)
Chao Li,1 Xiaofen Ma,2 Mengshi Dong,2 Yi Yin,1 Kelei Hua,1 Meng Li,2 Changhong Li,2 Wenfeng Zhan,2 Cheng Li,2,3 Guihua Jiang2 1Department of Medical Imaging, The Affiliated Guangdong No 2 Provincial People’s Hospital of Southern Medical University, The Third Clinical Medical College of Southern Medical University, 2Department of Medical Imaging, 3Department of Renal Transplantation, The Affiliated Guangdong No 2 Provincial People’s Hospital of Southern Medical University, Guangzhou, People’s Republic of China Objective: Investigating functional specialization is crucial for a complete understanding of the neural mechanisms of primary insomnia (PI). Resting-state functional magnetic resonance imaging (fMRI) is a useful tool to explore the functional specialization of PI. However, only a few studies have focused on the functional specialization of PI using resting-state fMRI and results of these studies were far from consistent. Thus, the current study aimed to investigate functional specialization of PI using resting-state fMRI with amplitude of low frequency fluctuations (ALFFs) algorithm. Methods: In this study, 55 PI patients and 44 healthy controls were included. ALFF values were compared between the two groups using two-sample t-test. The relationship of abnormal ALFF values with clinical characteristics and duration of insomnia was investigated using Pearson’s correlation analysis. Results: PI patients showed lower ALFF values in the left orbitofrontal cortex/inferior frontal gyrus, right middle frontal gyrus, left inferior parietal lobule, and bilateral cerebellum posterior lobes, while higher ALFF values in the right middle/inferior temporal that extended to the right occipital lobe. In addition, we found that the duration of PI negatively correlated with ALFF values in the left orbitofrontal cortex/inferior frontal gyrus, and the Pittsburgh Sleep Quality Index score negatively correlated with ALFF values in the left inferior parietal lobule. Conclusion: The present study added information to limited studies on functional specialization and provided evidence for hyperarousal hypothesis in PI. Keywords: primary insomnia, amplitude of low frequency fluctuations, resting-state fMRI, spontaneous brain activity